Legal impact and criminal challenges of the spread of false information on social media in the digital era - Gultom, Maidin; Flora, Henny Saida; Munawwarah, Siti; Simbolon, Netty Mewahaty; Endrawati, Eka Ari (Institute Of computer Science (IOCS), 2025)
The purpose of this research is to examine the criminal difficulties and legal ramifications of the modern era's epidemic of disinformation on social media in an effort to come up with thorough answers to these issues. The proliferation of hoaxes and other forms of misinformation has threatened Indonesia's social, political, and economic stability in recent years, thanks to the proliferation of social media and other forms of online communication. Another major problem with prosecuting hoaxers is the difficulty of law enforcement in the digital sphere, which includes factors like the anonymity of the offenders, different interpretations of rules, and the general public's lack of competence with digital technology. A descriptive-analytical technique is used in the research method of normative legal studies. In order to find problems and provide answers, this study compares applicable rules with international standards, namely the Criminal Code and the Electronic Information and Transactions Law. Laws, judicial judgments, and other primary legal documents are complemented by secondary legal items such as scholarly publications and literature. The study's findings reveal that despite the existence of laws like the Electronic Information and Transactions Law, its execution is often hindered by the international character of cyberspace and the dearth of funding for digital forensics tools. To combat these issues, the report suggests more adaptable regulation updates, societal efforts to increase digital literacy, technological advancements for law enforcement, and international collaboration. Additionally, law enforcement must strike a balance between protecting individuals' right to free speech and discouraging criminal behavior